2017
DOI: 10.1002/adhm.201700306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Functionalization, and Design of Magnetic Nanoparticles for Theranostic Applications

Abstract: In order to translate nanotechnology into medical practice, magnetic nanoparticles (MNPs) have been presented as a class of non‐invasive nanomaterials for numerous biomedical applications. In particular, MNPs have opened a door for simultaneous diagnosis and brisk treatment of diseases in the form of theranostic agents. This review highlights the recent advances in preparation and utilization of MNPs from the synthesis and functionalization steps to the final design consideration in evading the body immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
171
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 1,066 publications
(798 reference statements)
0
171
0
Order By: Relevance
“…The nanobiotechnology is promisingly based on the eco-friendly and green routes [6,7]. The biogenic routes have considered as leading paths to get the desired product having a specific shape, size, and surface chemistry, which are still challengeable in the chemical routes [8,9]. The synthesis of noble metal NPs using plant extract as a reducing agent is advancing the topic due to their remarkable applications in medicine sector [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The nanobiotechnology is promisingly based on the eco-friendly and green routes [6,7]. The biogenic routes have considered as leading paths to get the desired product having a specific shape, size, and surface chemistry, which are still challengeable in the chemical routes [8,9]. The synthesis of noble metal NPs using plant extract as a reducing agent is advancing the topic due to their remarkable applications in medicine sector [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These particles have large magnetic moments and are widely used as T2 contrast agents in MRI. T2 agents alter the transverse relaxation times (T2) of water protons and provide dark negative signal intensity in images [5].…”
Section: Biomedical Applications Of Spionsmentioning
confidence: 99%
“…Furthermore, numerous studies have reported that patients with PCa receiving neural drugs (-blockers) are at a decreased risk of recurrence and mortality (33)(34)(35). Thus, the drug-loading properties of the nanoprobe (36,37) were harnessed to load a neural drug serving as a nerve blocker in PCa, thus facilitating interventions in PCa with high nerve density and improving nanoprobe effectiveness and usability. Together, we exploited a nanoprobe that enabled not only visualization of nerve density but also targeting delivery of neural drug to inhibit tumor progression.…”
Section: Introductionmentioning
confidence: 99%